Emergence of BCR–ABL1 Fusion in AML Post–FLT3 Inhibitor-Based Therapy: A Potentially Targetable Mechanism of Resistance – A Case Series - Alotaibi, Ahmad S.; Yilmaz, Musa; Loghavi, Sanam; DiNardo, Courtney; Borthakur, Gautam; Kadia, Tapan M.; Thakral, Beenu; Pemmaraju, Naveen; Issa, Ghayas C.; Konopleva, Marina; Short, Nicholas J.; Patel, Keyur; et al. (Frontiers in Oncology, 2020)
Despite the promising result with FLT3 inhibitors in AML, the emergence of resistance poses a significant challenge, leading to a shorter response duration and inferior survival. This is frequently driven by on-target or parallel prosurvival mutations. The emergence of BCR–ABL1 as a mechanism of possible clonal evolution in relapsed AML has rarely been reported. Here we report our experience with three patients who had emergent BCR–ABL1 fusion at relapse after FLT3 inhibitors–based therapies. The first patient was refractory to multiple lines of therapies, including FLT3 inhibitors–based therapy. Patients 2 and 3 showed some response to combined FLT3-inhibitor and BCR–ABL targeted therapy (gilteritinib and ponatinib). The availability of effective targeted therapies for BCR–ABL1 makes this an important aberration to proactively identify and possibly target at relapse post–FLT3-inhibitor therapies.